Withdrawn: The main pillar: Assessment of space weather observational asset performance supporting nowcasting, forecasting, and research to operations. Issue 7 (1st July 2013) - Posner, A.; Hesse, M.; St. Cyr, O. C.
Key Points: Manuscript assesses current and near‐future space weather assets Current assets are inadequate for forecasting of severe geomagnetic storms Near‐future assets will not improve the situation